Baseline Moisture Resistance of PWP Cement Composite Boards Reinforced with Internal Glass Fiber Reinforcement under Accelerated Wet-Dry Aging. (5th August 2014) - Prachasaree, Woraphot; Piriyakootorn, Sitthichai; Limkatanyu, Suchart; Hawa, Abideng
Abstract : The purpose of this study was to improve the mechanical characteristics and moisture resistance of parawood particle (PWP) cement composite board developed by the authors. PWP cement composites were prepared with a mixture containing 15.0% parawood particles, 43.0% cement, 41.2% water, and 0.86% CaCl2 (by weight) and the PWP cement composite boards were internally reinforced with bidirectional glass fiber woven roving [0°/90°]. The board properties were evaluated under accelerated aging with wet-dry cycles to establish the durability and moisture resistance and the effect on flexural strength of the composite boards. The mechanical characteristics determined were the equivalent modulus of rupture (eMOR), the equivalent modulus of elasticity (eMOE), and the deformability factor (DF). The experimental results suggest that the strength and stiffness of the PWP composite boards with internal reinforcement are four times higher than those of the original PWP composite boards under accelerated aging based on 100 wet-dry cycles, implying better durability of the boards in outdoor use. The results provide a baseline to which improved formulations and reinforcements or designs can be compared using the same measurement methodology.